2012
DOI: 10.1002/cncr.27519
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori induces promoter methylation of E‐cadherin via interleukin‐1β activation of nitric oxide production in gastric cancer cells

Abstract: BACKGROUND:Helicobacter pylori infection causes gastric mucosal inflammatory responses, resulting in up-regulation of interleukin1b (IL-1b) and overproduction of mutagenic nitric oxide (NO). The authors previously demonstrated that IL-1b plays an important role in H. pylori-induced E-cadherin (E-cad) methylation. Here, they extend the study to investigate the downstream effect of IL-1b on H. pylori-induced gastric inflammation and aberrant DNA methylation. METHODS: Human gastric cancer cell lines (MKN7, MKN74,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 25 publications
3
68
0
Order By: Relevance
“…The results of the present study additionally support the mechanism of H. pylori-induced epigenetic changes and gastric carcinogenesis via IL-1β activation of iNOS and NO production, as proposed in our previous studies (5,17,18). Excessive NO production causes tissue damage with subsequent cellular genome injuries (10).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the present study additionally support the mechanism of H. pylori-induced epigenetic changes and gastric carcinogenesis via IL-1β activation of iNOS and NO production, as proposed in our previous studies (5,17,18). Excessive NO production causes tissue damage with subsequent cellular genome injuries (10).…”
Section: Discussionsupporting
confidence: 91%
“…This methylation induction effect could be reversed following the administration of IL-1β antagonist, interleukin-1 receptor antagonist (5,17,18). These findings suggest the potential mechanistic basis of H. pylori in induction of epigenetic changes for gastric diseases.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Similar to our study, Ando and colleagues (21) reported that miR-124a is silenced by aberrant DNA methylation in gastric cancer as well as H. pylori-infected, noncancerous gastric epithelium, favoring the field cancerization model. The mechanisms by which H. pylori promotes DNA hypermethylation of tumor-suppressor genes in gastric cancer are not entirely clear, but chronic inflammation induced by H. pylori infection, which triggers infiltration of monocytes and production of reactive oxygen and nitrogen species, appears to be involved in methylation induction (22,23). In this regard, it would be intriguing to explore whether such epigenetic dysregulation of miRNAs might contribute to chromatin remodeling in the development of other malignancies that arise in the context of microbially initiated inflammatory states (24).…”
Section: Discussionmentioning
confidence: 99%